1988
DOI: 10.1086/209149
|View full text |Cite
|
Sign up to set email alerts
|

What Does Familiarity Breed? Complexity as a Moderator of Repetition Effects in Advertisement Evaluation

Abstract: This article examines how consumers' attitudes toward advertisements are affected by their previous exposure to them. The results of our experiment suggest that the effects of exposure on ad attitudes may be moderated by the complexity of the advertisement: evaluations of complex ads become more positive with exposure, while those of simple ads do not. This finding may help explain why previous studies of ad exposure effects have yielded mixed results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 22 publications
4
85
1
2
Order By: Relevance
“…The survey measured the following constructs: brand complexity (adopted from Cox & Cox, 1988), identity-fit (Brown & Rafaeli, 2007), attractiveness of identification (Osgood, Suci, & Tannenbaum, 1957), optimal distinctiveness and identification (Bhattacharya & Sen, 2003), satisfaction , attachment (Zenker & Gollan, 2010), and positive word-of-mouth (Carroll & Ahuvia, 2006)dsee appendix for all used items. All items were measured with a 7-point Likert scale ranging from 1 ("I fully disagree") to 7 ("I fully agree") with one exception: identity-fit was measured using a VENN-diagram.…”
Section: Sample and Methods (Study 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…The survey measured the following constructs: brand complexity (adopted from Cox & Cox, 1988), identity-fit (Brown & Rafaeli, 2007), attractiveness of identification (Osgood, Suci, & Tannenbaum, 1957), optimal distinctiveness and identification (Bhattacharya & Sen, 2003), satisfaction , attachment (Zenker & Gollan, 2010), and positive word-of-mouth (Carroll & Ahuvia, 2006)dsee appendix for all used items. All items were measured with a 7-point Likert scale ranging from 1 ("I fully disagree") to 7 ("I fully agree") with one exception: identity-fit was measured using a VENN-diagram.…”
Section: Sample and Methods (Study 1)mentioning
confidence: 99%
“…When the brand itself is simple, consumers with little information at hand can more accurately identify the brand, but they may also show more dissatisfaction with the brand and a higher need for more information (Scammon, 1977). In addition, it appears that advertisements that are more complex receive results that are more positive: Research has found that complex advertisements are evaluated more positively and receive a higher number of exposures than simpler advertisements (Cox & Cox, 1988;Janiszewski & Meyvis, 2001). Since a place to live is highly important for nearly every aspect of life, we propose that individuals are willing to invest effort in information-seeking and processing.…”
Section: Identification and Complexitymentioning
confidence: 99%
“…For example, it has been observed that pre-exposure has the strongest influence on explicit preference when stimuli are presented during encoding for relatively short durations (e.g., Bornstein & DÕAgostino, 1992), with low pre-exposure frequency (e.g., Van den Bergh & Vrana, 1998), or when the stimuli used are complex (Bornstein, Kale, & Cornell, 1990;Cox & Cox, 1988. It also appears that people sometimes prefer novel to familiar stimuli (Fenske, Raymond, & Kunar, 2004), complex rather than simple figures (Berlyne & Crozier, 1971), and so on.…”
Section: Introductionmentioning
confidence: 99%
“…For attitude to the brand, the review yielded two dominant bipolar items: good/bad and like/dislike (Cox & Cox, 1988;Curlo & Ducoffe, 1998;Kempf & Smith, 1998). The latter was chosen, in the form of a 7-point semantic differential scale anchored at "I don't like it at all" and "I like it a lot".…”
Section: Methodsmentioning
confidence: 99%